The Guidelines for VUCA World Participative Supervision Development of the Schools in Bangmunnak Union under the Office of Secondary Educational Service Area Phichit - Nakpranboon, Cholticha; Sittirach, Thanakit (Journal of Buddhist Education and Research (JBER), 2025)
This research employed a mixed-methods approach with the objectives of (1) studying the current conditions and challenges of participatory supervision in the era of global disruption at schools under the Bang Mun Nak Cluster, Secondary Educational Service Area Office Phichit, and (2) proposing development guidelines for such supervision. The sample included 162 school administrators, teachers, and educational personnel, as well as 9 experts. Data were collected through questionnaires and interviews, and analyzed using frequency, percentage, mean, standard deviation, and content analysis. Findings revealed that the overall level of participatory supervision was high (𝑥̅ = 3.75). The highest rated aspect was joint implementation of supervision (𝑥̅ = 3.79), followed by joint feedback meetings (𝑥̅ = 3.77), joint planning (𝑥̅ = 3.74), and joint evaluation and conclusion (𝑥̅ = 3.71), respectively. The proposed development guidelines include: (1) in the planning stage, supervisors and supervisees should collaborate based on real conditions, integrating technology to enhance instructional quality; (2) during implementation, a supportive working atmosphere should be fostered, with training in technology use and innovation to increase effectiveness and encourage active participation; (3) evaluation and conclusion should be conducted in a positive environment, utilizing appropriate tools and promoting knowledge sharing; (4) feedback meetings should emphasize technology, communication, and language skills through training and practice, alongside the creation of learning communities and continuous evaluation. The results suggest that effective supervision in the era of global disruption requires collaboration at all stages - planning, implementation, evaluation, and feedback - within a supportive atmosphere, utilizing appropriate technology and innovation, with skill development and active participation from all stakeholders.